JENIS-JENIS KURIKULUM DARI BERBAGAI SUDUT PANDANG - Nasmin, Andi Nur Asnani; Yusran, Muh; Azisah, St; Wayong, Moh (Department of Islamic Education Management, 2024)
This study aims to find out the Types of Curriculum from Various Viewpoints. The research method used is qualitative research, namely data sourced from several articles, journals and reading books as well as experiences related to the focus of research, namely Types of Curriculum from Various Points of View. So that all data collected is then analyzed according to research needs. The discussion of this research discusses several things including: (1) Understanding the Curriculum, (2) Types of Curriculum, (3) Curriculum from Various Viewpoints. The conclusion in this study is that education is an important aspect in the formation of human character and quality. The curriculum is a guide that organizes learning activities, covering various elements such as objectives, content, methods, and evaluation. In Indonesia, curriculum evolution reflects a paradigm shift in education from the 1947 Curriculum to the 2023 Merdeka Curriculum, which provides freedom in curriculum design according to the local context. Although diverse, all types of curricula aim to influence student development according to educational goals, while facing implementation challenges such as teacher readiness and dense material.